MENINGKATKAN TATA BAHASA INGGRIS DENGAN MENGGUNAKAN METODE EGRA - Marnina Marnina (Musamus Journal of Language and Literature, 2018)
The research aimed to find out whether EGRA (Exposure, Generalization, Reinforcement, Application) method can improve the students’ achievement and interest in learning English grammar. This research was done in SMP BP Al-Munawaroh in May Academic Year 2018/2019. The population of this research was conducted at the students of SMP BP Al-Munawaroh, and the samples were 35 students of Eight Grade of SMP BP Al-Munawaroh selected purposively sampling. The data were collected by using test, questionnaire and observation. The data from the test and questionnaire were analyzed quantitatively while the data from the observation were analyzed qualitatively. The result of the analyzes show that EGRA Method gives higher improvement on students’ English Grammar. The mean score of in pretest 40,78 (poor) to to 61,89 (good) in post-test. The finding from questionnaire verifies that the highest rank of the mean score is 43,71% agreed students; 22,29% strongly agreed students; 14,86% of neutral answer and 17,43% of disagreed students and 1,71% students answer the strongly disagree statement. EGRA Method is responded positively by the English grammar and the application is preferable. Keywords: EGRA method; English grammar; achievement